Analisis Potensi dan Permasalahan Pariwisata Berbasis Community-Based Tourism di Wilayah Jolosutro, Desa Srimulyo, Kecamatan Piyungan, Kabupaten Bantul, Daerah Istimewa Yogyakarta - Faiz Rahmatullah Nugroho; Yutia Cesarinda Kusumawati; Adinda Putri; Alfiana Amrin Rosyadi (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Jolosutro is one of the hamlets in Piyungan District, Bantul Regency that has various tourism development potentials. These potentials are due to the fact that Jolosutro is closely related to the history of Sunan Geseng, its heritage sites, cultural activities, and local gastronomy. This study aims to analyze the potentials and problems in Community-Based Tourism (CBT) planning in the Jolosutro area. This research uses an applied qualitative approach with the Napak Tilas method in the form of observation, documentation, and focus group discussions. Napak Tilas Sunan Geseng was conducted together with the local community, the tourism awareness group (Pokdarwis), Srimulyo Village Government, and KKN-PPM UGM 2023 team. This method was chosen to be developed for several reasons, such as being able to implement the CBT concept, maintaining the continuity of local wisdom, having the opportunity to present experience-based tourism to tourists, and having the potential to provide economical welfare for the community. However, based on the Strength, Weakness, Opportunity and Threat (SWOT) analysis, there is still a need for some improvement of this tourism, including road access issues, supporting facilities at each site, as well as maintenance and revitalization of existing sites.